Railway as Long-Term Integration Factor of 2 I st Century Croatia and Europe - Bogović, Blaž; Stipetić, Antun; Badanjak, Dragan (Promet - Traffic&Transportation)
The paper considers the need for COilSt/Ucting high-speedrailway lines in Croatia that would represent a part of Europeanhigh-speed railway network. The economic value of theseprojects is studied and highlighted, within the technological developmentof Croatia, with high-speed tracks as prerequisite forintegration into the European exchange flows.Considering the traffic component of Croatia, scientific researchis proposed, as well as determining and defining of optimalsolutions for the const/Uction of high-speed railway tracks.